Application of the method of automatic alignment and combining adjacent images in fundus imaging - Licznerski, Tomasz; Jamrozy-Witkowska, Agnieszka; Ćwirko, Marek; Kosz, Dariusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
The paper presents a method for automatic alignment and combining adjacent images of the fundus. Presented algorithm is based on specific arrangement of the vessels in the fundus. A correlation function is used to the adjacent images with extracted net of the vessels. An optimum location of the images is found by applying successive approximations method. An angle of rotation and shift of the combining images are taken into an account during this search. The paper shows also the examples of application of the method in fundus imaging.